1994
DOI: 10.1002/humu.1380040204
|View full text |Cite
|
Sign up to set email alerts
|

Non-phenylketonuria hyperphenylalaninaemia in Northern Ireland: Frequent mutation allows screening and early diagnosis

Abstract: Up to 10% of newborn children with a positive Guthrie test have non-phenylketonuria hyperphenylalaninaemia, i.e., mild elevation of serum phenylalanine that does not require dietary treatment. Depending on the relative frequencies of different phenylalanine hydroxylase mutations in a particular population, non-PKU HPA is usually caused by the combined effect of a mild HPA mutation and a severe PKU mutation. Presented here is a comprehensive analysis of non-PKU HPA in Northern Ireland. Of particular interest is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
(9 reference statements)
0
15
0
2
Order By: Relevance
“…The pattern of MHP mutations, with a prevalence of A403V (16.7%), differs from that in other populations; in Denmark the predominant MHP mutation is D415N, 24 in Sicily the highest frequency corresponds to A300S 11 and in Ireland to T380M. 25 In the course of this study, four patients were found to present no mutations in the analysed regions of the PAH gene. Although mutations elsewhere in the gene Genotypes and phenotypes of PKU in Spain LR Desviat et al t could not be definitely ruled out, a PAH deficiency was finally discarded, considering that the phenylalanine levels were borderline (125-180 µM) with the generally accepted threshold for dietary intervention.…”
Section: Discussionmentioning
confidence: 54%
“…The pattern of MHP mutations, with a prevalence of A403V (16.7%), differs from that in other populations; in Denmark the predominant MHP mutation is D415N, 24 in Sicily the highest frequency corresponds to A300S 11 and in Ireland to T380M. 25 In the course of this study, four patients were found to present no mutations in the analysed regions of the PAH gene. Although mutations elsewhere in the gene Genotypes and phenotypes of PKU in Spain LR Desviat et al t could not be definitely ruled out, a PAH deficiency was finally discarded, considering that the phenylalanine levels were borderline (125-180 µM) with the generally accepted threshold for dietary intervention.…”
Section: Discussionmentioning
confidence: 54%
“…A322G appears to be a frequent MHP mutation in Sweden, but homozygosity for the mild PKU mutation Y414C was also identified . T380M is the prevalent MHP mutation in Northern Ireland [Zschocke et al, 1994]. Common MHP mutations in Germany include V245A, A403V, and I306V [Weglage et al, 2001].…”
Section: Mhp Mutationsmentioning
confidence: 99%
“…[6][7][8][9] Correlations between the genotype and clinical phenotype of PKU have been demonstrated using predicted PAH activity, which is the average in vitro PAH activity for both mutations, 10 with several mutations related to non-classical PKU phenotypes (mild PKU and mild hyperphenylalaninemia (HPA)). 7,[11][12][13] Recently, BH 4 -responsive PAH deficiency was defined by decreased blood phenylalanine after a BH 4 loading test 14 and patients with this deficiency were treated with long-term BH 4 . [15][16][17][18][19][20] Blood phenylalanine levels were relatively well controlled by BH 4 therapy compared with dietary treatment involving improvement of patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%